Adenophora liliifolia: Condition of its Populations in Central Europe - Prausová, Romana; Marečková, Lucie; Kapler, Adam; Majeský, L’uboš; Farkas, Tünde; Indreica, Adrian; Šafářová, Lenka; Kitner, Miloslav (Walter de Gruyter GmbH, 2016)
This study deals with populations of the European-South-Siberian geoelement Adenophora liliifolia (L.) A. DC. in the Czech Republic, Slovakia, Hungary, Romania, and Poland, where this species has its European periphery distribution. We studied the population size, genetic variability, site conditions, and vegetation units in which A. liliifolia grows. Recent and historical localities of A. liliifolia were ranked into six vegetation units of both forest and non-forest character. A phytosociological survey showed differences in the species composition among localities. Only a weak pattern of population structure was observed (only 22% of total genetic variation present at the interpopulation level, AMOVA analysis), with moderate values for gene diversity (Hj = 0.141) and polymorphism (P = 27.6%). Neighbor joining and Bayesian clustering suggest a similar genetic background for most of the populations from Slovakia, the Czech Republic, and Poland, contrary to the populations from Hungary, Romania, as well as two populations from Central and South Slovakia. This might be explained by a relatively recent fragmentation of the A. liliifolia populations in Central Europe. Nevertheless, it seems that several populations in Romania, South Hungary, and Slovakia were isolated for a longer period of time and their genetic differentiation is more evident.
Keywords: AFLP; Campanulaceae; European periphery distribution; declining population; EuropeanSouth-Siberian geoelement; genetic variability; vegetation